Dietary chromium yeast supplementation length in diets for growing-finishing pigs - Sanches,Danilo de Souza (2021)
ABSTRACT This study aimed to evaluate different periods of chromium yeast (CrY) supplementation on growth performance and quantitative carcass characteristics of growing-finishing pigs. We used eighty barrows (Duroc/Pietran × Large White/Landrace) with an initial body weight of 24.5±2.4 kg. A completely randomized block design was used within four periods of dietary CrY supplementation (control diet: CrY-free, from 25 to 110 kg; Cr25-110 kg: diet with 0.4 mg kg−1 of CrY, from 25 to 110 kg; Cr50-110 kg: diet with 0.4 mg kg−1 of CrY, from 50 to 110 kg; and Cr70-110 kg: diet with 0.4 mg kg−1 of CrY, from 70 to 110 kg), with ten replicates and two animals each. The CrY supplementation did not affect (P>0.05) either the grow performance or the carcass characteristics evaluated. The dietary supplementation of 0.4 mg kg−1 of CrY for growing-finishing pigs (25 to 110 kg) does not alter the performance neither the quantitative carcass characteristics.